MATHEMATICS LEARNING PLATFORM FOR MALAYSIAN PRIMARY SCHOOL STUDENTS - MOHD, NUR FATIN SYAFIQAH (IRC, 2019)
Aligned with technological advancement of this era, this paper presents a framework to learn Mathematics for Malaysian primary school students aged from 10 until 12 years old through Mathematics learning platform. In Malaysia, most of primary school students learn Mathematics through class-based and there is no specific Mathematics learning platform is being introduced at primary school level. Plus, absence of Mathematics teachers make the primary school students are not able to learn Mathematics effectively when they are outside of school hours. Hence, the main objective of this project is to develop a Mathematics learning platform to connect the Malaysian primary school students and Mathematics experts, and to integrate the pedagogical approaches in the Mathematics learning platform. It is designed in such way where the primary school students can ask the problematic Mathematics question in the learning platform and the question will be answered by the experts. The answer by the experts will be verified by the system admin before it becomes visible to all user to ensure only correct answer and provide the right references for the primary school students. With this Mathematics learning platform, it can help the Malaysian primary school students to learn Mathematics effectively even outside of school hours.